(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
The term carcinoid was first employed by Oberndorfer in 1907 to describe a group of tumours of the gastrointestinal tract that had a relatively indolent course and that were considered to be intermediate between adenoma and carcinoma in malignant potential. Gastrointestinal carcinoid tumours are a type of cancer that form in the lining of the gastrointestinal tract originating from entero-chromaffin like (ECL) cells. Gastric carcinoid tumours are rare tumors that develop within the gastric mucosa. They can present as an isolated lesion or there can be multiple lesions. The tumours can invade locally into deeper structures of the gastrointestinal tract (GIT) wall. Solitary gastric carcinoids have a greater chance for the development of malignancy and metastases as compared to multiple gastric carcinoids due to hypergastrinemia. A 60 years old man presented with abdominal pain, vomiting and weight loss and was found to have carcinoid tumour of stomach without classic carcinoid syndrome (CS). Despite advances in the understanding of patho-physiology of carcinoid tumour its complications remain enigmatic. Early, accurate diagnosis and aggressive treatment is recommended. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 145-148